Cycling anatomy - Sovndal, Shannon, 1970- (Champaign, IL : Human Kinetics, 2009)
See what it takes to maximize cycling power, speed, and endurance! Cycling Anatomy will show you how to improve your performance by increasing muscular strength and optimizing the efficiency of every movement. Cycling Anatomy features 74 of the most effective cycling exercises, each with clear, step-by-step descriptions and full-color anatomical illustrations highlighting the primary muscles in action. Cycling Anatomy goes beyond exercises by placing you on the bike and into the throes of competition. Illustrations of the active muscles involved in cornering, climbing, descending, and sprinting show you how the exercises are fundamentally linked to cycling performance. From steep inclines to slick terrains, Cycling Anatomy will ensure you're prepared for any challenge that comes your way. You'll also learn how to modify exercises to target specific areas, reduce muscle tension, and minimize common cycling injuries. You'll also learn ways to pull it all together to develop a training based on your individual needs and goals. Whether you're training for an upcoming century ride or just want to top that killer hill with strength to spare, Cycling Anatomy will make sure you get the most out of every ride.
Keywords: Cycling -- Physiological aspects; Cycling -- Training -- Charts, diagrams, etc; Cycling -- Training; Fysiologie; Training; Wielersport